Rational Emotive Behavior Therapy: Role-Playing Techniques to Enhance Emotional Intelligence and Empathy - M. Zuhdi Zainul Majdi; Zainul Holil; Desti Ekawati (Universitas Islam Negeri Madura, 2025)
Intelligence is the ability to acquire and use knowledge in order to solve problems and adapt to the environment. A person's high intelligence should be accompanied by high academic ability as well, but in reality, high IQ does not necessarily guarantee high academic achievement or learning outcomes. At most, IQ contributes about 20% to the factors that determine success in life, while 80% is determined by other factors including emotional intelligence. This explains that a person's success is not only influenced by intellectual intelligence but also by emotional intelligence. Individuals with emotional intelligence are able to monitor their feelings well, and they can control their emotions, one of which is having a high level of empathy. Emotional intelligence is the ability of an individual to motivate themselves and persevere in facing frustration, control impulsive urges, which are urges that arise based on mood, and delay gratification, regulate their mood so that it does not affect their ability to think and empathize. The purpose of the research is to determine the effectiveness of rational emotive behavior counseling using role-playing techniques to enhance emotional intelligence and empathy. This study uses a one-group pretest-posttest design. The subjects in this study, totaling 14 people, were divided into 2 groups. The sampling method used is purposive sampling. Data were collected using emotional intelligence and empathy questionnaires. Data analysis used MANOVA statistical tests. The research results show that rational emotive behavior counseling using role-playing techniques is effective in enhancing emotional intelligence and empathy.